Long-term Observation of Porous Sapphire Dental Implants - Takahashi, Toshiyuki; Miho, Otoaki; Tsunoda, Masatake; Nakagawa, Kan-Ichi; Sato, Toru; Suzuki, Yuta; Hisanaga, Ryuichi (Bulletin of Tokyo Dental College, 2008)
We used porous sapphire dental implants made of alumina clinically for 4 years 1 month, commencing September, 1984 until September, 1988. Subjects consisted of 18 men and 42 women 20-71 years old (mean age: 35 years). Sixty-five implants were inserted in 60 patients. Of these, 20 were clinical cases of an implant connected with natural teeth and 45 were free-standing cases. We conducted a follow-up study on these patients over a 23-year period. One implant in 1 patient had to be removed because of postoperative infection and 8 implants in 7 patients had to be removed because of fracturing or detachment of the porous-part. This paper reports 3 cases where implants remained in place for 21-23 years. These cases have all shown good long-term clinical progress.